Budesonide repairs decreased barrier integrity of eosinophilic nasal polyp epithelial cells caused by PM2.5 - Siyuan Ma; Mu Xian; Yang Wang; Chengshuo Wang; Luo Zhang (Clinical and Translational Allergy, 2021)
Abstract Background Eosinophilic chronic rhinitis with nasal polyps (eos‐CRSwNP) is a subtype of nasal polyps (NPs) characterized by severe type‐2 inflammation and defective epithelial barrier function. The epithelial barrier plays important roles in the pathogenesis of NPs and type‐2 inflammation. Particular matter 2.5 (PM2.5) are fine particles with a diameter less than 2.5 μm, containing a mixture of different components. Here, we investigated the impact of PM2.5 on the barrier function of the eos‐CRSwNP epithelium and explored the reparative function of budesonide. Methods Samples from noninflammatory nasal mucosa and eos‐CRSwNP were collected to establish an in vitro air–liquid interface cultured model. The cells were exposed to PM2.5 at 50 or 100 µg/ml intermittently for 72 h, with or without budesonide pretreatment. Barrier function and tight junction (TJ) expression were reflected by measuring transepithelial resistance (TER), paracellular flux permeability of fluorescein isothiocyanate‐labeled 4‐kDa dextran, quantitative real‐time polymerase chain reaction (qPCR), and immunofluorescence staining of TJ proteins. Cytokine expression was measured by qPCR and enzyme‐linked immunosorbent assay or Luminex. Results PM2.5 increased paracellular flux and downregulated TJ protein expression (zona occuldens‐1, occludin, and claudin‐1), but did not change TER. These changes could be partially restored by budesonide treatment. Interleukin (IL)‐8, IL‐10, IL‐1α, and tissue inhibitor of metalloproteinase (TIMP)‐1 concentrations were significantly increased in the culture medium of cells exposed to PM2.5, and budesonide significantly reduced the changes in IL‐8, IL‐1α, and TIMP‐1. Conclusion PM2.5 impaired the barrier function of eos‐CRSwNP epithelial cells and increased the permeability of large molecules. PM2.5 also increased the secretion of pro‐inflammatory cytokines by nasal epithelial cells. Budesonide could partially repair the damage, suggesting potential applications in clinical practice.